2019
DOI: 10.3390/molecules24142572
|View full text |Cite
|
Sign up to set email alerts
|

Approach Study for Mass Balance of Pesticide Residues in Distillers’ Stillage along with Distillate and Absence Verification of Pesticides in Distilled Spirits from Pilot-Scale of Distillation Column

Abstract: Herein, contaminants remaining in distillate and distillers’ stillage were quantitatively measured after distillation. After rice bran powder was contaminated with 10 ppm of lead (Pb) and cadmium (Cd) or 0.02–1.27 ppm of five pesticides (terbufos, fenthion, iprobenfos, flutolanil, and ethoprophos) followed by fermentation, single-stage distillation was performed. In the obtained distillate, no Pb or Cd was found, as expected. However, when the pesticides were added as contaminants, trace–0.05 ppm of some pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previously, we reported that substances (e.g., pesticides) could migrate to the distillate depending on the distillation method and conditions [14]. In the case of mycotoxins, barley soju obtained through a small-scale distillation process was studied, in which mycotoxins did not migrate into the barley soju when distilled at an atmospheric pressure and at a low pressure (100 mmHg) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that substances (e.g., pesticides) could migrate to the distillate depending on the distillation method and conditions [14]. In the case of mycotoxins, barley soju obtained through a small-scale distillation process was studied, in which mycotoxins did not migrate into the barley soju when distilled at an atmospheric pressure and at a low pressure (100 mmHg) [15].…”
Section: Introductionmentioning
confidence: 99%